Distal pancreatic resection via laparo-endoscopic single site surgery – development of the technique - Michał Orłowski; Paweł Lech; Maciej Bobowicz; Maciej Michalik (Videosurgery and Other Miniinvasive Techniques)
Aim: To present a novel technique of a laparo-endoscopic single site (LESS) distal pancreatic resection via the umbilicuswith use of the QuadPortTM Access System.Material and methods: The technique of distal pancreatic resection through a 30 mm longitudinal incision in theumbilicus is described. Medial to lateral approach of pancreas preparation using a harmonic scalpel and regularlaparoscopic instruments is applied. The described technique was successfully applied in a 26-year-old female patientwith tumour of the pancreatic body and tail (90/41/27 mm). Pancreatectomy was followed by splenectomy due toinfiltration of the splenic vessels.Results: Total operative time was 160 min. Blood loss was 800 ml. Initial wound size was 30 mm. Splenic vein andartery infiltration forced augmentation of the wound to 80 mm. The patient required only per request medication.Peristalsis returned spontaneously on the first postoperative day. Hospital stay was 4 days. There were no early perioperativecomplications. The patient required readmission due to electrolyte imbalance 7 weeks after the operation.Conclusions: The proposed operative technique of single incision laparoscopic distal pancreatectomy is difficult andchallenging. Nonetheless, the authors proved that it is safe and feasible when performed by an experienced laparoscopicteam.